Higher Order Fractional Variational Symmetric Duality Over Cone Constraints - Khatri, Sony; Prasad, Ashish Kumar (Yugoslav Journal of Operations Research; Vol 33 No 2 (2023), 2022)
The article aims at higher order fractional variational pair of symmetric dual formulations where constraints are defined over cones and explores pertinent duality output applying the idea of higher order $η$-invexity. Also, we bring into begin a numerical example in order to validate the definition exploited to establish duality results. Moreover, we demonstrate a case study dealing with the static formulation of our considered problem and explore the results carefully.